Immune response against influenza in a cohort of repeatedly vaccinated adults during the 2017/2018 and 2018/2019 seasons - Guiomar, Raquel (2024)
Funding Information: We would like to acknowledge all the participants from the staff of the National Institute of Health for their participation in the present study and their donation of blood samples for the evaluation of the humoral immunity response after vaccination during 2017/2018 and 2018/2019 seasons. We acknowledge Anabela Cordeiro, assistant at the Department of Occupational Medicine, National Institute of Health Dr. Ricardo Jorge, IP, for the management support. Publisher Copyright: © 2024 by the authors.